احادیث متعارضہ کے اختلاف کو تطبیق کے ذریعے دور کرنے کا امام طحاوی کا اسلوب: Al-Ṭaḥāwī’s Approach to Resolve Contradiction in Ḥadīths through Compatibility (Al-Qamar, 2021)
Contradictory Ḥadīth is a term that is used in Ḥadīth sciences when two or more Ḥadīths seem to be opposite to one another. Abu Ja’far al-Ṭaḥāwī (d321/933) has tried to resolve the contradiction of Ḥadīths through nullification, preference and compatibility in his book Sharaḥ M’āni al-Athār. The question arises that how he resolved the contradiction of the Ḥadīths through compatibility. In this article, his method of conformity has been discussed with examples from his said book. He resolved the contradiction of Ḥadīths reported about right of pre-emption for neighbor by saying that these prophetic traditions explain one another. He also identified the meanings of Ḥadīths reported about fasting after mid of Sha’bān and resolved the difference with conformity. He also discussed the matter of breaking fast due to wet cupping (Ḥijama) and resolved the contradiction of the Ḥadīths.
Keywords: Ḥadīths; Contradiction; al-Ṭaḥāwī; Conformity; Sharaḥ M’āni al-Athār